2020
DOI: 10.1177/0284185120902381
|View full text |Cite
|
Sign up to set email alerts
|

T1rho and T2 mapping of ankle cartilage of female and male ballet dancers

Abstract: Background Since ballet dancers begin their training before skeletal maturity, accurate and non-invasive identification of cartilage diseases is clinically important. Angle-dependent analysis of T1rho and T2 sequences can be useful for quantification of the composition of cartilage. Purpose To investigate the angle-dependent T1rho and T2 profiles of ankle cartilage in non-dancers and dancers. Material and Methods Ten female non-dancers, ten female dancers, and 9 male dancers were evaluated using T1rho and T2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Ankle MRI allows noninvasive evaluation of macroscopic and ultrastructure composition/organization cartilage changes. 10,11 Quantitative MRI such as T2, 10-13 T2*, 14 T1rho, 15 dGEMRIC, 11,16 sodium, 17 and gagCEST 18 mapping provide compositional information about cartilage tissue health and repair tissue quality, 17,19,20 while morphological sequences provide information about macroscopic characteristics such as synovitis, chondral/osteochondral lesions, subchondral bone cysts, and bone marrow edema. 10,11,21…”
Section: Introductionmentioning
confidence: 99%
“…Ankle MRI allows noninvasive evaluation of macroscopic and ultrastructure composition/organization cartilage changes. 10,11 Quantitative MRI such as T2, 10-13 T2*, 14 T1rho, 15 dGEMRIC, 11,16 sodium, 17 and gagCEST 18 mapping provide compositional information about cartilage tissue health and repair tissue quality, 17,19,20 while morphological sequences provide information about macroscopic characteristics such as synovitis, chondral/osteochondral lesions, subchondral bone cysts, and bone marrow edema. 10,11,21…”
Section: Introductionmentioning
confidence: 99%
“…Spannow et al [23] also showed a sex-specific difference in male and female adolescents by ultrasound examination in 2010. Regional and gender variations of ankle cartilage characteristics were found in dancers and non-dancers, with male dancers showing larger cartilage thickness than female dancers and non-dancers [24]. Furthermore, when examining the tibial articular cartilage of the knee joint, a 13% greater cartilage volume was measured in male subjects [25], which had a substantial influence on the study results.…”
Section: Discussionmentioning
confidence: 93%
“…23 It must be noted that the magic angle effect has a major influence on T2 and T1ρ relaxation in articular cartilage so that relaxometric data strongly depend on fiber orientation and anisotropy. 37,38 However, this effect is less pronounced for T1ρ than for T2 relaxation. 37 While the sensitivity to fiber anisotropy benefits the detection of cartilage degeneration, which is usually associated with a loss of anisotropy, the sensitivity to fiber orientation may encumber studies with comparative relaxometric measurements, for example, longitudinal studies.…”
Section: Discussionmentioning
confidence: 96%
“…A T1ρ protocol was chosen for this relaxometric study since in a previous work on comparative T2 and T1ρ mapping of the patellofemoral cartilage with in situ loading, T1ρ could be more reproducibly measured 23 . It must be noted that the magic angle effect has a major influence on T2 and T1ρ relaxation in articular cartilage so that relaxometric data strongly depend on fiber orientation and anisotropy 37,38 . However, this effect is less pronounced for T1ρ than for T2 relaxation 37 .…”
Section: Discussionmentioning
confidence: 99%